NAVIGATING A MULTICULTURAL WORLD: EQUIPPING TEENAGERS WITH INTERCULTURAL COMMUNICATION SKILLS (American Journal of Pedagogical and Educational Research, 2024)
In this fast-changing society, young individuals are urged to be strong in intercultural relationships to survive and develop. This article explores how to train youngsters to be equipped with cultural understanding, respect other nations, and communicate through diverse cultural backgrounds is important. By offering several strategies to raise cultural awareness, this paper concludes the necessity of intercultural competencies in teenagers’ lives in an increasingly multicultural global community.